Linking Ethical Awareness to Transparency: The Mediating Effect of Ethical Decision-Making - Widijaya; Ariyanto Richard Pratama (Global Financial Accounting Journal, 2024)
This study aims to determine the impact of ethical awareness and ethical decision-making on transparency. The population in this study comprises employees working in public accounting firms and tax consulting firms in Batam City. The data collection method employed a Likert scale questionnaire. The data analysis methods used multiple linear regression with the SPSS 22 program (Statistical Package for the Social Sciences). The results indicated that ethical awareness has a significant positive effect on ethical decision-making. Both ethical awareness and ethical decision-making have a significant positive effect on transparency.